Numerical simulation of heat transfer in microchannel using energy conservative dissipative particle dynamics - Yelei Xie; Shuo Chen (Advances in Mechanical Engineering, 2015)
Dissipative particle dynamics is a particle-based mesoscopic simulation method. Classic dissipative particle dynamics cannot be used to simulate heat transfer in fluids since the total energy of the system is not conserved. In this article, two-dimensional unsteady heat conduction is first investigated using dissipative particle dynamics with energy conservation. The energy conservative dissipative particle dynamics results are compared with the FLUENT simulation data, and it demonstrates that they are in good agreement with each other. Then, forced convection heat transfers in microchannel of the same wall temperature and different wall temperatures are simulated, respectively, by using periodic boundary condition of dimensionless temperature. The results show that the velocity, temperature, and dimensionless temperature distributions are consistent with theoretical results. Finally, we give a qualitative analysis about the applicability of the energy conservative dissipative particle dynamics approach in simulating flow and heat transfer in rough microchannel.